2016
DOI: 10.1213/ane.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short-Term Propofol and Dexmedetomidine on Lung Mechanics, Histology, and Biological Markers in Experimental Obesity

Abstract: In this model of diet-induced obesity, a 1-hour propofol infusion yielded increased airway resistance, atelectasis, and lung inflammation, with depletion of antioxidative enzymes. However, unlike sodium thiopental and propofol, short-term infusion of dexmedetomidine had no impact on lung morphofunctional and biological variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In restrictive lung disease, the possible effect of dexmedetomidine was not well investigated in humans. In an animal model of experimental obesity, dexmedetomidine administration showed better morphological and functional lung characteristics compared to propofol [ 4 ]; thus, we hypothesized that a similar effect could be present in humans. Morbidly obese patients are characterized by the high prevalence of restrictive lung disease [ 5 ]; thus, we investigated the effects of dexmedetomidine infusion on oxygenation (P/F ratio) as well as lung mechanics (compliance and dead space) in a selected group of morbidly obese patients with restrictive lung disease, to find out the possible benefits of this drug on this population.…”
Section: Introductionmentioning
confidence: 99%
“…In restrictive lung disease, the possible effect of dexmedetomidine was not well investigated in humans. In an animal model of experimental obesity, dexmedetomidine administration showed better morphological and functional lung characteristics compared to propofol [ 4 ]; thus, we hypothesized that a similar effect could be present in humans. Morbidly obese patients are characterized by the high prevalence of restrictive lung disease [ 5 ]; thus, we investigated the effects of dexmedetomidine infusion on oxygenation (P/F ratio) as well as lung mechanics (compliance and dead space) in a selected group of morbidly obese patients with restrictive lung disease, to find out the possible benefits of this drug on this population.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we used a well-established metabolic programing model of obesity, which, compared with other models based on dietary interventions (Heil et al, 2016;Maia et al, 2019), better resembles the major hallmarks of clinical obesity (Plagemann et al, 2009). The difference in body weight between obese and non-obese animals, although modest, was significant (p = 0.0006).…”
Section: Discussionmentioning
confidence: 99%
“…Gelafundin R 4% (B. Braun, São Gonçalo, RJ, Brazil) was administered intravenously (in 0.5-mL increments) as needed to maintain mean arterial pressure (MAP) >60 mmHg. Depth of anesthesia was evaluated by the response to light touch with a fingertip on the rat's whiskers (0 = awake, fully responsive to surroundings; 1 = not responsive to surroundings, rapid response to whisker stimulation; 2 = slow response; 3 = unresponsive to whisker stimulation), pupil diameter, position of the nictitating membrane, and movement in response to tail stimulation (Heil et al, 2016). Experiments were started when responses to a noise stimulus (handclap), whisker stimulation, and tail clamping were absent.…”
Section: Animal Preparation and Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that, apart from cardioprotective effects, 1 h of propofol (but not dexmedetomidine) infusion increased airway resistance and pulmonary inflammation, in an effect mediated by expression of TNF-α and IL-6 in lung tissue[ 129 ]. These results raised questions about the proposed mechanisms of propofol or its lipid vehicles on obesity-associated metainflammation.…”
Section: Immunomodulatory Effects Of Anesthetics In Obesitymentioning
confidence: 99%